Pemberdayaan Masyarakat Dalam Mengatasi Kenakalan Remaja Di Kecamatan Koto Tangah Kota Padang - Julianti, Isti Dwi; Putra, Maulana Rizky Arya; Ayura, Sanju Prety; Hanoselina, Yulia; Helmi, Rahmadhona Fitri (Jurnal Ilmu Sosial, Humaniora dan Seni, 2025)
Community empowerment in Koto Tangah District, Padang City, is carried out through collaborative methods involving various components of society, educational institutions, security forces, and local government. In order to form a young generation with morals, this initiative seeks to provide a place for constructive activities for them to participate, such as planning extracurricular activities centered on local sports and culture and strengthening customary and religious values. Supervision, counseling, and character building of students together both inside and outside of school is one way that educational institutions and the police can work together to help prevent and overcome juvenile delinquency. One example is the cooperation agreement signed by the Madrasah and the Koto Tangah Police. The main objective of Community Empowerment in Koto Tangah District is to foster a young generation that is independent, disciplined, and has character in accordance with local and religious values. To achieve this goal, stakeholders must work together, community capacity must be strengthened, and positive spaces and activities must be provided for teenagers. Especially in Koto Tangah District, Padang City, juvenile delinquency is a major social problem that threatens public security and order. Through participatory and collaborative strategies involving the government, community leaders, educational institutions, and families, this study seeks to evaluate community empowerment in overcoming juvenile delinquency.